Difucosylation of chitooligosaccharides by eukaryote and prokaryote α1,6-fucosyltransferases - Ihara, Hideyuki; Hanashima, Shinya; Tsukamoto, Hiroki; Yamaguchi, Yoshiki; Taniguchi, Naoyuki; Ikeda, Yoshitaka (Biochimica et biophysica acta, 2013)
The synthesis of eukaryotic N-glycans and the rhizobia Nod factor both involve α1,6-fucosylation. These fucosylations are catalyzed by eukaryotic α1,6-fucosyltransferase, FUT8, and rhizobial enzyme, NodZ. The two enzymes have similar enzymatic properties and structures but display different acceptor specificities: FUT8 and NodZ prefer N-glycan and chitooligosaccharide, respectively. This study was conducted to examine the fucosylation of chitooligosaccharides by FUT8 and NodZ and to characterize the resulting difucosylated chitooligosaccharides in terms of their resistance to hydrolysis by glycosidases. The issue of whether FUT8 or NodZ catalyzes the further fucosylation of chitooligosaccharides that had first been monofucosylated by the other. The oligosaccharide products from the successive reactions were analyzed by normal-phase high performance liquid chromatography, mass spectrometry and nuclear magnetic resonance. The effect of difucosylation on sensitivity to glycosidase digestion was also investigated. Both FUT8 and NodZ are able to further fucosylate the monofucosylated chitooligosaccharides. Structural analyses of the resulting oligosaccharides showed that the reducing terminal GlcNAc residue and the third GlcNAc residue from the non-reducing end are fucosylated via α1,6-linkages. The difucosylation protected the oligosaccharides from extensive degradation to GlcNAc by hexosamidase and lysozyme, and also even from defucosylation by fucosidase. The sequential actions of FUT8 and NodZ on common substrates effectively produce site-specific-difucosylated chitooligosaccharides. This modification confers protection to the oligosaccharides against various glycosidases. The action of a combination of eukaryotic and bacterial α1,6-fucosyltransferases on chitooligosaccharides results in the formation of difucosylated products, which serves to stabilize chitooligosaccharides against the action of glycosidases. [Display omitted] •Difucosylated chitooligosaccharides (GNFF′) were synthesized via the action of FUT8 and NodZ.•GNFF′ are fucosylated at the reducing end and the third GlcNAc from the non-reducing end.•The GNFF′ were found to be resistant to the action of some exo- and endo-type glycosidases.